Honey clinically stimulates granulation and epithelialization in chronic wounds: a report of two cases (Faculty of Medicine Universitas Indonesia, 2018)
Various studies have been widely reintroduced honey as a wound dressing in chronic wound treatment. However, its utilization in Indonesia is still very limited. This study reported the effect of honey in stimulating the epithelialization and granulation on chronic wound treatment in our center. Two chronic wound cases, diabetic foot ulcer patient and gangrenous extravasation due to sodium bicarbonate, were daily treated with honey applications. After six-week evaluation, clinically the tissue granulation and epithelization were seen at the edge of the observed wounds and decreased the wound size significantly with no reported side effects. Honey clinically stimulates the epithelialization and granulation on chronic wound treatment.